Validation of smart device-based assessment of sit-to-stand - Carnal, Matthew J., author; Tracy, Brian L., advisor; Reiser, Raoul F., II, committee member; Gilkey, David, committee member (Colorado State University. Libraries, 2017)
The sit-to-stand (STS) field test provides a relatively crude (timed or counted) outcome measure when assessing daily functional activity and quality of life. Coupling the current STS test with commercially available mobile smart device applications that can sample, store, and wirelessly transmit data strengthen the test by adding speed, velocity, and potentially power through the built in IMU. Expensive lab-based biomechanics equipment is required to obtain measures of leg power (LP) for individual repetitions during STS tasks. Modern smart devices are inexpensive, portable, user friendly, and contain sensitive inertial sensors that contain accelerometers and a gyroscope. The purpose of this study was to determine the ability of the smart device equipped IMU through the use of its gyroscope to detect movement across varying speeds, and make comparisons with an electro goniometer (eGONI) and force platform. Forty-two young adults (22.9 ± 2.9 years) performed three trials of a modified STS, which included five fast STS repetitions followed by fifteen successively deliberate decelerated repetitions to mimic fatigue in the elderly. A 5th generation iPod Touch was firmly attached (Velcro) to a strap around the lower thigh. An eGONI (Biometrics) was placed laterally across the knee joint. The feet were on a force platform (AMTI Accusway) in front of the chair. Concurrently, iPod gyroscope data (rad), knee joint angle (rad), and ground reaction force (GRF, N) were sampled at 100Hz. The peak slope (0.1s time constant) of the iPod pitch signal, eGONI signal, and GRF was calculated for the rising phase of each rep. For each device, the max, min, and max-min across the 20 reps were calculated for the three trials. Correlations and Bland Altman analyses were computed between the devices for all subjects combined and individually to assess R2 distributions for all trials. The iPod Touch versus the two devices aforementioned was highly correlated when comparing peak slopes of the devices output measures (rad/s, N/s). The iPod Touch measured angular speed similarly to the eGONI which is considered a gold standard found in research laboratories looking at the kinematics of joint movements. The force platform, which is a gold standard commonly used to measure muscular power peak slopes aligned with the iPod Touch's providing evidence the iPod Touch's metric of angular speed correlates with power though the devices are measuring different units. As measured with the iPod, min and max rising speeds are easily detected during the 20 STS fast to progressively slowing STS protocol. The iPod based gyroscope is sufficiently sensitive to detect differences in chair rising angular speed at the thigh and can replace an electronic goniometer and force plate for assessing slow and ballistic chair rising speeds.